Prinsip Keadilan Hakim Dalam Sejarah Kenabian - Fausya, Annisa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This paper explores the principles of justice applied by the prophets throughout prophetic history, particularly Prophet Muhammad (PBUH), Prophet David (AS), and Prophet Solomon (AS). These prophets are known for upholding justice in dispute resolution, regardless of social status or personal interest. Using a qualitative literature study approach, this research reveals that prophetic values of justicesuch as objectivity, equality, wisdom, and protection of the weakare highly relevant as a source of inspiration for modern legal systems. The enforcement of justice should not only be legalistic, but also ethical and spiritual, in order to build a more civilized judiciary. This study recommends the integration of prophetic justice principles into legal education and contemporary judicial reform.